Comparative modeling of hull form resistance for three ocean going vessels using methodical series - Samson, Nitonye; Sidum, Adumene (International Journal of Engineering and Technology, 2015)
This paper presents a comparative estimation of the hull form resistance for Cargo ship, Ocean-going Tug and Container ship. The research study evaluates the influences of various ship hull parameters in relations to the vessel speeds and level of turbulence (Reynolds number). The modeling was done using MATLAB software and the model test technique based on the ITTC, ATTC, Granville and Hughes friction line application. The result shows that the hull form resistances follow the same trend in the ITTC, ATTC and Granville models, while the Hughes model gave a different trend with other techniques. It further revealed that as the speed increases by 10knots, the frictional resistance coefficients decrease by 11.86% for the ITTC & Granville models, and 12.03% for the Hughes model. For Ocean-going Tug and Container Ship, the frictional resistance coefficient decrease by 12.31% for the ITTC & Granville models, and 12.14% for the Hughes model. The Reynolds number increase by 62.52% for every 10knots increase in the speed of the Cargo ship and 62.23% for every 10knots increase in the speed of the Ocean going tug and Containership. At various experimental speeds, the results showed that for every 1 knots increase in the speed of the Containership, the effective power developed increases by 9.45%. This provides a technical and analytical guide on hull form resistance trend for engineers and ship operators.